Perbandingan Metode Pembelajaran NHT dan STAD pada Kemampuan Pemecahan Masalah Matematika - Ayi Ahmad Maulana Yusup (SAP (Susunan Artikel Pendidikan), 2022)
Mathematical problem fixing capability is one of the factors in attaining the desires of arithmetic education. Problem solving is the management of a problem using a method as a result of which it succeeds in finding the desired goal. Innovative learning is expected to increase mathematical problem-solving skills and be able to form students excited in learning. In the learning process using nht learning examples and STAD learners are actively involved. This study aims to find out the differences in students' mathematical problem-solving skills through nht and STAD type cooperative learning models. This research is experimental. The samples on this experimental were students of SMP Darussalam which consisted of 2 classes with 35 students in each class. The results of the study discovered that there are differences in students' mathematical problem-solving skills through nht and STAD type cooperative learning models. Both examples are effectively used in the learning of linear equations.